Cost of work-related injuries in insured workplaces in Lebanon - Fayad Rim; Nuwayhid Iman; Tamim Hala; Kassak Kassem; Khogali Mustafa (Bulletin of the World Health Organization, 2003)
OBJECTIVE: To estimate the medical and compensation costs of work-related injuries in insured workplaces in Lebanon and to examine cost distributions by worker and injury characteristics. METHODS: A total of 3748 claims for work injuries processed in 1998 by five major insurance companies in Lebanon were reviewed. Medical costs (related to emergency room fees, physician consultations, tests, and medications) and wage and indemnity compensation costs were identified from the claims. FINDINGS: The median cost per injury was US$ 83 (mean, US$ 198; range, US$ 0-16 401). The overall cost for all 3748 injuries was US$ 742 100 (76% of this was medical costs). Extrapolated to all injuries within insured workplaces, the overall cost was US$4.5 million a year; this increased to US$ 10 million-13 million when human value cost (pain and suffering) was accounted for. Fatal injuries (three, 0.1%) and those that caused permanent disabilities (nine, 0.2%) accounted for 10.4% of the overall costs and hospitalized injuries (245, 6.5%) for 45%. Cost per injury was highest among older workers and for injuries that involved falls and vehicle incidents. Medical, but not compensation, costs were higher among female workers. CONCLUSION: The computed costs of work injuries - a fraction of the real burden of occupational injuries in Lebanon - represent a considerable economic loss. This calls for a national policy to prevent work injuries, with a focus on preventing the most serious injuries. Options for intervention and research are discussed.